Object-Oriented and Classical Software Engineering - R Schach Stephen (Mcgraw Hill, 2004)
Classical and Object-Oriented Software Engineering, 6/e is designed for an introductory software engineering course. This book provides an excellent introduction to software engineering fundamentals, covering both traditional and object-oriented techniques.